Analisis Perlakuan Diskriminatif terhadap Tokoh Utama dalam Serial Drama Korea "True Beauty" yang Berbasis Kecantikan - Messy Permata Putri; Juliana Kurniawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The Korean drama True Beauty portrays a vivid reflection of the social reality where beauty standards significantly influence how women are treated in society. This study investigates how these standards lead to discrimination against individuals who do not align with socially constructed ideals of appearance. Specifically, it focuses on the representation of such discrimination in the character of Im Ju Kyung, a high school student who is constantly judged for her natural look. Utilizing a qualitative approach with Roland Barthes' semiotic theory, this research deciphers three levels of meaning—denotative, connotative, and mythological—embedded within selected scenes from episodes 1 and 3. The findings indicate that Ju Kyung encounters six distinct forms of appearance-based discrimination: verbal bullying, physical bullying, non-verbal bullying (such as gestures or facial expressions), social exclusion, beauty privilege (where attractive individuals receive favorable treatment), and internalized social pressure to conform. Each discriminatory act is not only rooted in visual representations but also carries deeper ideological implications—suggesting that physical beauty is a prerequisite for social acceptance and personal value. Although True Beauty critiques the culture of appearance-based discrimination, it simultaneously perpetuates the myth that transformation through makeup or cosmetic procedures is a viable solution to gain acceptance. This duality reflects the complex role of media as both a mirror of societal norms and a tool that reinforces dominant ideologies. In doing so, the drama raises critical questions about the ethical responsibilities of popular culture in shaping perceptions of gender, identity, and worth based on physical appearance. Through this analysis, the study contributes to discussions on media literacy and body politics in contemporary Korean pop culture.